What lies beneath the euro's effect on financial integration? Currency risk, legal harmonization, or trade? - Sebnem Kalemli-Ozcan; Elias Papaioannou; José-Luis Peydró (European Central Bank (ECB), 2010)
Although recent research shows that the euro has spurred cross-border financial integration, the exact mechanisms remain unknown. We investigate the underlying channels of the euro's effect on financial integration using data on bilateral banking linkages among twenty industrial countries in the past thirty years. We also construct a dataset that records the timing of legislative-regulatory harmonization policies in financial services across the European Union. We find that the euro's impact on financial integration is primarily driven by eliminating the currency risk. Legislative-regulatory convergence has also contributed to the spur of cross-border financial transactions. Trade in goods, while highly correlated with bilateral financial activities, does not play a key role in explaining the euro's positive effect on financial integration.
Keywords: F1; F3; G2; K0; 330; euro; European Union; financial integration; FSAP; law and finance; regulation; Trade; Europäische Integration; Finanzmarkt; Europäisches Währungssystem; Euro; Währungsrisiko; EU-Staaten